Natural History of Transposition in the Green Alga Chlamydomonas reinhardtii: Use of the AMT4 Locus as an Experimental System - Kim, Kwang-Seo (Copyright © 2006 by the Genetics Society of America, 2006)
The AMT4 locus of the green alga Chlamydomonas reinhardtii, which we mapped to the long arm of chromosome 8, provides a good experimental system for the study of transposition. Most mutations that confer resistance to the toxic ammonium analog methylammonium are in AMT4 and a high proportion of spontaneous mutations are caused by transposon-related events. Among the 15 such events that we have characterized at the molecular level, 9 were associated with insertions of the retrotransposon TOC1, 2 with a small Gulliver-related transposon, and 1 with the Tcr1 transposon. We found that Tcr1 is apparently a foldback transposon with terminal inverted repeats that are much longer and more complex than previously realized. A duplication of Tcr1 yielded a configuration thought to be important for chromosomal evolution. Other mutations in AMT4 were caused by two mobile elements that have not been described before. The sequence of one, which we propose to call the Bill element, indicates that it probably transposes by way of a DNA intermediate and requires functions that it does not encode. The sequence of the other and bioinformatic analysis indicates that it derives from a miniature retrotransposon or TRIM, which we propose to call MRC1 (miniature retrotransposon of Chlamydomonas).